Current research on methamphetamine: Epidemiology, medical and ‎psychiatric effects, treatment, and harm reduction efforts - Seyed Ramin Radfar ‎; Richard A. Rawson ‎ (Addiction and Health, 2014)
Background: Methamphetamine (MA) which is known as “shisheh” in Iran is a drug that widely is used in many parts of the world and it is near to a decade that is available for the most drug users and has a considerable prevalence of use. Due to high abuse prevalence and very new challenging phenomenon, it is very important that researchers and treatment providers become more familiar with different aspects of MA. Discussion: It has multiple neurobiological impacts on the nervous system, some of which are transitory and some longer lasting. MA activates the reward system of the brain and produces effects that are highly reinforcing, which can lead to abuse and dependence. Routes of administration that produce rapid onset of the drug’s effects (i.e., smoking and injection) are likely to lead to more rapid addiction and more medical and psychiatric effects. No effective pharmacotherapies have been developed for the treatment of MA dependence; although, this is an area of very active research. Several behavioral treatments have been shown to reduce MA use, but better treatments are needed. Conclusion: Harm reduction strategies for non-treatment seeking MA users are needed to reduce the risk of human immunodeficiency virus and other medical risks. The research agenda for MA is substantial, with development of effective pharmacotherapies as one of the most important priorities. Appropriate and effective response for prevention, treatment and harm reduction services due to increasing problems regarding MA in Iran and some other countries in the region.